SOCIAL IMPACT OF FOREIGN IMMIGRANTS IN AFFORDABLE HOUSING AREA. CASE STUDY: MENTARI COURT, SELANGOR, MALAYSIA - Hoon Leh, Oliver Ling; Mohd Rosli, Nik Nurul Farahanis; Marhalim, Farah Ayuni; Mohamed Musthafa, Siti Nur Afiqah (PLANNING MALAYSIA, 2017)
Social impact can be defined as the net effect of an activity on a community and the well-being of individuals and families in the community. Among the activities that give rise to social impacts is the influx of foreign immigrants into a locality. This study examines the impacts of foreign immigrants’ presence on the local society at an affordable housing area in Selangor. A questionnaire survey was carried out among respondents that were selected from the local residents to examine impacts on family relationship, the relationship among local residents, the relationship between locals and foreigner, acceptance of foreigners by local residents, sense of belonging, housing price, job opportunity, and safety. Overall, the results show that most of the respondents felt that the presence of foreign immigrants in the study area has negatively affecting them with regard to family and community relationship, sense of belonging, safety and housing price/rental.